To study an awareness on sustainable green building practices amongst construction industry players - Md. Yassin, Azlina; Musa, Sharifah Meryam Shareh; Shafii, Haryati (Academic Research Publishing Group, 2018)
Green building is refers to both a structure and the using processes that are environmentally responsible and resource efficient throughout the building’s life cycle. Green building concept is introduced in 1960s and has gradually spread throughout the world and emphasized more on to energy conserving for office building in 1970s. In Malaysia, the green building concept has been accepted after announcement of 9th Malaysian Plan (2006-2010) in 2006 with focusing more on Renewable Energy (RE) and Energy Efficiency (EE). Furthermore, Malaysia has launched its own Green building Index (GBI) in year 2009. However this GBI is concentrated only on the measurement of green building but not for other aspects of green building such as indoor environmental quality, sustainable site planning and management, and so on. Moreover, the development of green building concept has occurred with limited understanding and guidance, and some cases have added a cost to the development. Therefore, this paper aims to identify factor influencing green building practice in Malaysia as well as to study awareness on green building practices amongst construction industry practitioner. The findings of this research were based on the questionnaires mailed and e-mailed to 75 construction industry companies; Property development company, Contractor company, Architect firm and Property management company within Klang Valley area. The findings have identified independent/government rating system as the main factor influencing construction industry player to undertaking green building practice. The results also revealed that the awareness amongst the construction players towards sustainable green building concept is moderate, and property development companies contributed to the highest mean score. These results show the willingness of the respondents to participate and committed with the green building development. This will allow recommendations to help ensure more sustainable green building development in Malaysia in the future.